THE EFFECT OF COLLABORATIVE LEARNING STRATEGY AND LEARNING MOTIVATION OF LEARNING RESULTS ISLAMIC EDUCATION OF ISLAMIC ELEMENTARY SCHOOL STUDENTS STATE 057212 KECAMATAN HINAI LANGKAT REGENCY - Rabiatun Adawiyah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
The objectives of this research were to find out: (1) the different effectbetween colaborrative and competitive instructional strategy towardIslamic Education achievement, (2) the difference of the Islamic Educationachievement between student with high learning motivation and lowlearning motivation, and (3) the interaction between instructional strategy and learning motivation toward Islamic Education achievement. The population of this research was all students of Grade V SDN 057212Hinai consisting of two classes. The sampling technique applied wascluster random sampling taught with colaborrative instructional strategyand the students taught with competitive instructional strategy. Theinstrument used to measure the Islamic Education achievement was amultiple choice test. The instrument used to measure the students’learning motivation was questionnaire. The normality test used Lilieforsand the homogeneity test was Fisher test and Bartlett test. The dataanalysis technique was Analysis of Variance with two-way at the level ofsignificance  = 0,05 followed by Scheffe test. The research findings were:(1) on average the students’ Islamic Education achievement taught withcolaborrative instructional strategy was higher than the average the students’ Islamic Education achievement taught with competitiveinstructional strategy, , (2) on average the student’ Islamic Educationachievement with high learning motivatione was higher than the student’Islamic Education achievement with low learning motivation, and (3)there was an interaction between instructional strategy and learningmotivation toward Islamic Education achievement.